2021
DOI: 10.1093/jpepsy/jsab128
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Well-Sibling Communication in Families With a Child Who Has a Life-Limiting Condition: Quantitative Survey Data

Abstract: Objective Living with a child with a life-limiting condition (LLC), for which there is no hope of cure and premature death is expected, places much stress on a family unit. Familial communication has the potential to serve as a buffer when children are faced with stressful situations. The overall aim of the study was to learn more about illness-related communication between parents and well-siblings, giving particular consideration to the amount of illness-related communication, and sibling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The importance of talking with someone is consistent with other studies reporting that communication between parents and siblings is one of the most critical factors in siblings adapting to life with an ill child (Jaaniste et al, 2020 ; Marklund et al, 2018 ), and leading to siblings feeling less alone (Eaton Russell et al, 2018 ; Lövgren et al, 2020 ). Siblings may struggle to speak about their feelings (Jaaniste et al, 2022 ) or avoiding initiating conversations to protect their parents from feeling sad or uncomfortable (Eaton Russell et al, 2018 ). In D’Urso et al ( 2017 ) study, all siblings reported that it was helpful once they had been able to talk and recommended it to other siblings (D’Urso et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of talking with someone is consistent with other studies reporting that communication between parents and siblings is one of the most critical factors in siblings adapting to life with an ill child (Jaaniste et al, 2020 ; Marklund et al, 2018 ), and leading to siblings feeling less alone (Eaton Russell et al, 2018 ; Lövgren et al, 2020 ). Siblings may struggle to speak about their feelings (Jaaniste et al, 2022 ) or avoiding initiating conversations to protect their parents from feeling sad or uncomfortable (Eaton Russell et al, 2018 ). In D’Urso et al ( 2017 ) study, all siblings reported that it was helpful once they had been able to talk and recommended it to other siblings (D’Urso et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…30 While some authors have found that brothers are more likely to develop externalizing problems, others have found that brothers may experience emotional struggles because they tend to receive less education-related communication from parents than sisters. 10,24,37 Additionally, researchers have found that sisters are generally more prone to internalizing problems, likely due to increased caregiving responsibilities at home, fewer social activities with peers, and a lack of parental attention. 36,38 However, our ndings revealed that sisters had more externalizing problems than brothers, possibly due to uncertainties in the initial phases of the child's condition.…”
Section: Discussionmentioning
confidence: 99%